Cross-cultural memoir as borderland negotiation of identity in language education. Issue 3 (3rd July 2019) - McPherron, Paul; McIntosh, Kyle
ABSTRACT: In this article, we discuss three cross-cultural memoirs used in three different university courses that introduced students to the complex identities that form both inside and outside of language classrooms. In arguing for the value of using such memoirs as content in university courses, we provide a detailed thematic analysis of Peter Hessler's River Town ; Elaine Mar's Paper Daughter ; and Binyavanga Wainaina's One Day I Will Write about This Place, and evaluate classroom activities and assignments that drew on these memoirs. Specifically, we highlight how reading them allowed students to understand fundamental themes in language learning and teaching and multiple ideological, institutional, and social levels of influence. Drawing on these frameworks, we make a case for employing cross-cultural memoirs to wrestle with the complexities inherent in teaching and learning English in courses across the curriculum.